Pengelolaan Limbah di Rumah Vita Insani Kota Pematangsiantar - Albenopri Simarmata; Romario F D Purba; Dian G Purba; Didi Syahputra; Putri Khairunnisa; Octa P Saragih; Hartati R Sitio; Savirgi B Amri; Brido S Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2024)
Liquid waste and solid waste originating from hospitals can function as a medium for spreading disorders or disease for staff, sufferers and the community. The research was carried out with the aim of finding out an overview of waste management at Vita Insani Hospital starting from sorting, containerization, lifting, temporary shelter, final disposal site. This research is quantitative research with an observational and descriptive approach, using descriptive research methods, the research was carried out with the aim of creating an objective picture or description of a situation at the Vita Insani Hospital, Pematangsiantar city regarding the management of solid and liquid medical waste. Research results: Overall waste processing at the Vita Insani Hospital, Pematang Siantar City is quite good, however improving the quality of processing is important regarding processing facilities and infrastructure through maintenance of each facility and infrastructure.